Karyotypes and Repetitive DNA Evolution in Six Species of the Genus Mahanarva (Auchenorrhyncha: Cercopidae) - Anjos, Allison [UNESP]; Rocha, Gabriela C. [UNESP]; Paladini, Andressa; Mariguela, Tatiane C. [UNESP]; Cabral-De-Mello, Diogo C. [UNESP] (Karger Publishers, 2016)
Insects of the Cercopidae family are widely distributed and comprise 59 genera and 431 species in the New World. They are xylemophagous, causing losses in agricultural and pasture grasses, and are considered as emerging pests. Chromosomally, these insects have been studied by standard techniques, revealing variable diploid numbers and primarily X0 sex chromosome systems (males). We performed chromosome studies in 6 Mahanarva (Cercopidae) species using standard and differential chromosome staining as well as mapping of repetitive DNAs. Moreover, the relationship between the repetitive DNAs was analyzed at the interspecific level. A diploid chromosome number of 2n = 19,X0 was documented, with chromosomes gradually decreasing in size. Neutral or GC-rich regions were detected which varied depending on the species. Fluorescence in situ hybridization with a (TTAGG)n telomeric motif probe revealed terminal signals, matching those of the Cot DNAs obtained from each species, that were also restricted to the terminal regions of all chromosomes. Dot blot analysis with the Cot fraction from M. quadripunctata showed that at least part of the repetitive genome is shared among the 6 species. Our data highlight the conservation of chromosomal features and organization of repetitive DNAs in the genus Mahanarva, suggesting a low differentiation for chromosomes and repetitive DNAs in most of the 6 species studied.
Keywords: Agricultural pests; Heterochromatin; Holocentric chromosomes; Repetitive DNAs; Telomeres